Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fvets.2019.00315
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Neutrophil Gelatinase-Associated Lipocalin Concentration in Canine Cerebrospinal Fluid and Serum and Its Involvement in Neuroinflammation

Abstract: Neutrophil gelatinase-associated Lipocalin (NGAL) is a glycoprotein involved in inflammation acting as an acute phase protein and chemokine as well as a regulator of iron homeostasis. NGAL has been shown to be upregulated in experimental autoimmune encephalomyelitis (EAE) in mice. Increased NGAL concentration in cerebrospinal fluid (CSF) and expression in central nervous system (CNS) has been described in human neuroinflammatory disease such as multiple sclerosis and neuropsychiatric lupus as well as in bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, elevated immunoglobulin A levels in serum and CSF serve as diagnostic tool ( 44 , 52 ). Levels of acute phase proteins such as C-reactive protein, serum amyloid A, haptoglobin ( 53 ), or neutrophil gelatinase-associated lipocalin ( 54 ) are elevated in the acute disease episode compared to non-inflammatory neurological diseases. Especially, CRP is used as a remission and therapy monitoring marker ( 55 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, elevated immunoglobulin A levels in serum and CSF serve as diagnostic tool ( 44 , 52 ). Levels of acute phase proteins such as C-reactive protein, serum amyloid A, haptoglobin ( 53 ), or neutrophil gelatinase-associated lipocalin ( 54 ) are elevated in the acute disease episode compared to non-inflammatory neurological diseases. Especially, CRP is used as a remission and therapy monitoring marker ( 55 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil Gelatinase-Associated Lipocalin (NGAL, also known as Lipocalin-2, or LCN2) is involved in several inflammatory pathways [ 28 ]. Its increased concentration in CSF is reported in patients with MS, especially those with secondary progressive MS and primary progressive MS compared to RRMS [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that NGAL can also be used as a marker of neuroin ammation and related behavioral dysfunction [15,16]. The increase of NGAL in brain tissue can aggravate amyloid-β-induced toxicity, leading to neurodegenerative changes in the brainstem nucleus [17]. Iron chelator has the potential to improve neurodegenerative changes and treat central nervous system diseases, but its neuroprotective effect may be related to patient's NGAL level [18].…”
Section: Introductionmentioning
confidence: 99%